Case Studies of Contemporary Crimes from an Islamic Law Perspective - Muhammad Farrel Aufa Nst; Nanda Syahputra (Jurnal Sahabat ISNU SU, 2024)
The acceleration of modern-day information technology acts as a double-edged sword, triggering a radical metamorphosis of conventional crime into contemporary cyber-based crime. This study aims to analyze the characteristics, typology, and causal factors of contemporary crime, as well as formulate the qualifications of crimes and the formulation of sanctions from the perspective of Indonesian positive law and Islamic Criminal Law (Fiqh Jinayah). The research method used is normative juridical with a conceptual approach and case studies of four crime typologies, namely online fraud, cyber-corruption, ransomware attacks, and the industrialization of hoaxes. The results show that contemporary crimes are characterized by de-territoriality, high anonymity, fluidity, and are included in the white-collar crime cluster triggered by the technological gap and the degradation of cyber ethics. Although Indonesian positive law has anticipated this crime through the instruments of the ITE Law, the Corruption Law, the Money Laundering Law, and Law No. 1 of 1946, the effectiveness of its enforcement is still hampered by the complexity of digital evidence and jurisdictional constraints. In the view of Islamic Jurisprudence, all of these contemporary crimes cannot be categorized as hudud or qisas-diyat because they do not fulfill rigid material requirements of sharia, such as the absence of physical storage restrictions (al-hirz) on data theft. Therefore, contemporary crimes are classified as Ta'zir crimes, where the authority to formulate sanctions and their formulation is completely handed over to the ijtihad of the ruler (ulil amri) in order to uphold the public interest (mashlahah mursalah) and fortify the pillars of al-maqasid al-khamsah.